Efficiency of tuna oil to modify meat quality and fatty acid profile in pork as affected by gender and slaughter weight - Jaturasitha S. (2014)
In order to determine the highest efficiency of tuna oil (TO) supplementation, 48 barrows and 48 gilts fed on diets containing 0 or 20 g TO/kg diet were fattened either to 90, 100 or 110 kg live weight (2×2×3- factorial design). Variables describing water-holding capacity and texture of the M. longissimus dorsi were generally not influenced by TO as such. With one exception in shear force, no significant interactions among experimental factors were found. Incorporation of highly unsaturated n-3 fatty acids increased with TO supplementation, but this at the cost of fat shelf life. The n-3 fatty acids were reduced in proportion with increasing slaughter weight. In contrast, gender differences in polyunsaturated fatty acids found in unsupplemented pigs (higher in gilts), were balanced by TO supplementation. In conclusion, TO-fed pigs should be slaughtered early, while there is no need to differentiate for gender.